Housing security: Placing Brazil's social housing program in a violent context - Frank I. Müller (Journal of Illicit Economies and Development (JIED), 2022)
Latin America's "housing crisis" affects 28 million lower-income households. In many Latin American countries, governments have developed housing policies to provide access to basic standard dwelling and to offer a route towards legal tenure at an affordable cost. Yet, they have failed to address violence and crime that beneficiaries are often exposed to. I argue that housing policies must take stronger efforts in accounting for urban security. To sustain that argument, I will trace Brazil's attempts to provide a "secure future for beneficiaries by providing equal access for all to physical and social infrastructure and basic services, as well as adequate and affordable housing" (UN Habitat 2017: 7). I refer to such policy directive as an incentive for national governments to pursue housing security. I primarily draw from academic literature on housing policies in Latin America, evaluations of Brazil's contemporary housing program, and media outlets, and use parts of my own interviews with public administrators and beneficiaries of the housing program. Designing routes towards housing security, first and foremost by reinforcing the constitutionally granted right to housing along with guaranteeing the social function of property, must be central concerns of Brazil's next federal government.
Keywords: 330; Social housing; security; crime; Brazil; Minha Casa Minha Vida; Rio de Janeiro